PENINGKATAN PRESTASI BELAJAR BAHASA INGGRIS MELALUI PEMBELAJARAN KOOPERATIF MODEL LEARNING BY DOING - Basuki Basuki (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2017)
This research was aimed to; (1) increase the ability of researcher in the scientific thinking on learning English, (2) increase the motivation to learn English in the eightth graders-E of the first state yunior high school at Kalitengah in writing and speaking skill, and (3) determine an increase of English learning in writing and speaking skill in the eightth graders E of the first state yunior high school at Kalitengah through Learning by Doing. The subjects of the research were the eightth graders-E of the first state yunior high school at Kalitengah in the academic year 2014/2015. The research was conducted in February 2015. The material presented was Text Procedure, short functional text such as: Announcement and short message. The result of the study was the cooperative learning model Learning By Doing had a positive impact in improving student achievement marked by increased mastery learning students in each cycle, the first cycle of 61.76%, 79.41% the second cycle, the third cycle 93.93%. Based on these data we could conclude that although the results of student learning not achieve maximum results, but it indicated the change towards a better direction. Thus the students' ability to understand the content of reading English texts and communicate through cooperative learning methods Learning By Doing models had been increased.